Does body mass index compromise assisted reproductive technique outcomes? A cross-sectional study - Fereshteh Bahrami; Saeideh Dashti; Esmat Mangoli; Hanie Sadat Hosseini (Shahid Sadoughi University of Medical Sciences, 2024)
Abstract Background: Overweight and obese people face several health problems. Female obesity has been shown to reduce fertility in the general population. Assisted reproductive technology outcomes in obese cases are widely studied, but the results are inconclusive. Objective: This study aimed to compare live birth rate (LBR) among women with 4 different types of body mass index (BMI). Materials and Methods: In this cross-sectional study, data of 1611 women, who were candidates for fresh and frozen embryo transfer cycles, was extracted from 2051 medical files at the Reproductive Sciences Institute, Yazd, Iran from May 2019-May 2021. The participants were divided into 4 groups (underweight, normal, overweight, and obese) according to their BMI, and LBR was considered to be the main outcome. Results: Of 1611 women, 39 were underweight, 585 were normal, 676 were overweight, and 311 were obese. Underweight women had the lowest LBR (12.8%), but there was no statistically significant difference (p = 0.55). In addition, LBR was compared in the 4 BMI groups according to age, type of transfer cycle (fresh or freeze), and cause of infertility, and there was comparable LBR in the 4 BMI groups. However, metaphase 2 oocyte rate, doses of gonadotropin usage in the cycles, and estradiol level had statistically significant differences (p < 0.001). Conclusion: According to our study, obesity does not affect LBR in the IVF cycle, regardless of fresh or frozen embryo transfer cycles, different age groups, and causes of infertility.